Synthesis of New Tetrazol-5-ylalkenyl Derivatives of Ferrocene by Wittig Olefination - Grodner, Jacek; Sałaciński, Tomasz (Synthesis, 2012)
An effective and straightforward method has been developed for the synthesis of new olefinic derivatives of ferrocene that contain tetrazole rings. The method is based on condensation of 1-formyl-, 1,1′-diformyl-, or (E)-1-(2-formylvinyl)ferrocene with 1-substituted [(triphenylphosphoranylidene)methyl]-1H-tetrazoles, which are readily prepared by treatment of the corresponding phosphonium salts with aqueous sodium hydroxide. The olefination reaction proceeds in a diastereoselective manner with formation of the corresponding (E)-alkenes or (E,E)-dienes as the exclusive or major products.
Keywords: iron; heterocycles; ylides; Wittig reactions; olefination; ferrocenes